The effects of production offshoring on R&D and innovation in the home country - Bernhard Dachs; Bernd Ebersberger; Steffen Kinkel; Oliver Som (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2014)
We investigate the effects of production offshoring on the innovation activities of manufacturing firms in the home country. The analysis is based on a dataset of more than 3000 manufacturing firms from seven European countries. We find that offshoring firms on average employ a higher share of R&D and design personnel, introduce new products more frequently to the market, and invest more frequently in advanced process technologies compared to non-offshoring firms. Concerns that offshoring may hurt innovation because of the lost links between production and product development are not supported by the evidence.
urn:nbn:de:0011-n-3672678
Keywords: F23; F61; O31; O33; 330; offshoring; R&D; home country effects; investment; product innovation; process innovation